A mechanism of abstraction for independent definition of game’s platform elements - Montenegro Marín, Carlos Enrique; Cueva Lovelle, Juan Manuel; Espada, Jordan Pascual (Visión electrónica, 2014)
This article is aimed at determining the feasibility of using a common mechanism to define the configuration in games for mobile devices. Such a configuration is intended to increase the level of abstraction up to a point where the definition of a platform game in XML format is made independent. This should then be read and deployed in an automatic way over any mobile platform.